2003
DOI: 10.1211/0022357021314
|View full text |Cite
|
Sign up to set email alerts
|

Hypochlorite scavenging activity of hydroxycinnamic acids evaluated by a rapid microplate method based on the measurement of chloramines

Abstract: Scavengers of hypochlorite (XOCl) could have beneficial effects in diseases in which this oxidant plays a pathogenic role. It has been reported that ferulic acid and chlorogenic acid, the quinic ester of caffeic acid, are good hypochlorite scavengers, but a systematic evaluation of the naturally occurring hydroxycinnamic acids (HCAs), which these substances belong to, has not been performed yet. Thus, in this work we studied, by two different in-vitro methods, the antioxidant activity of five HCAs: p-coumaric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 25 publications
4
48
0
2
Order By: Relevance
“…The authors postulated that the enhancement of activity is related to the electron-donation properties of the methoxy moiety that can stabilize the phenoxy radical formed in the reaction with free radicals. The superior activity of ferulic acid compared to para-coumaric acid has been observed also by other authors [47,124,125]. Addition of the second methoxy group (as in the structure of sinapic acid Fig.…”
Section: Introduction Of Electron Donating Substituentssupporting
confidence: 72%
See 4 more Smart Citations
“…The authors postulated that the enhancement of activity is related to the electron-donation properties of the methoxy moiety that can stabilize the phenoxy radical formed in the reaction with free radicals. The superior activity of ferulic acid compared to para-coumaric acid has been observed also by other authors [47,124,125]. Addition of the second methoxy group (as in the structure of sinapic acid Fig.…”
Section: Introduction Of Electron Donating Substituentssupporting
confidence: 72%
“…Addition of the second methoxy group (as in the structure of sinapic acid Fig. 1) further increases the activity, as deducted from the comparison of sinapic acid with ferulic acid in hypochlorite scavenging [47] and DPPH scavenging assays [125,126]. Similarly, the results of our group and others have demonstrated that esters of sinapic acid are more active than esters of ferulic acid in �-carotene-linoleic acid system [127] and in DPPH assay [126].…”
Section: Introduction Of Electron Donating Substituentssupporting
confidence: 71%
See 3 more Smart Citations